Failure of cost-benefit analysis in gastrointestinal endoscopy - Sonnenberg, Amnon; Bakis, Gennadiy (Endoscopy International Open, 2019)
Background and study aims We discuss the occurrence of two cases, where the endoscopic pursuit of diagnostic certainty resulted in adverse events that exceeded the clinical relevance of the endoscopic diagnosis itself. In both instances, physicians were hesitant to subject their patients to a necessary surgical intervention before gastrointestinal endoscopy had provided them with absolute assurance that no other mitigating factors could possibly jeopardize the success of a planned intervention. In trying to avoid a single and potentially bad outcome of a necessary medical intervention, the physicians exposed their patients to many more additional and unnecessary risks. As key players in clinical decision-making, physicians sometimes may find it difficult to disentangle their own risk-benefit considerations from those of their patients.